Analysis of the Adiwiyata Program in environmental awareness behavior at SMA Negeri 30 Jakarta - Yulista Kusuma Wardani; Indra Prabowo; Sudrajat Sudrajat (Educenter : Jurnal Ilmiah Pendidikan, 2026)
Environmental problems are still a key global concern for reaching the SDGs, highlighting the need to strengthen environmental awareness from an early age. One of the initiatives implemented by the Indonesian government is the Adiwiyata Program, which aims to develop environmentally responsible and sustainable school communities. This study aims to analyze the influence of the Adiwiyata Program on students’ environmental awareness behavior at SMA Negeri 30 Jakarta. The research employed a quantitative approach with a correlational design. Data were collected through a closed-ended questionnaire administered to 271 students from grades X, XI, and XII, selected using a purposive random sampling technique. Data were analyzed using bivariate correlation and regression analyses. The findings indicate that the Adiwiyata Program contributes to students’ environmental awareness, with varying levels of influence across the dimensions of environmental awareness, namely general beliefs and values, personal attitudes, and environmental knowledge. Overall, the program demonstrates a positive relationship with students’ environmental awareness behavior. The study suggests that future research should incorporate additional variables that may influence environmental awareness to develop a more thorough insight into the factors shaping student environmentally responsible conduct.